A Comparative Study: Michael Adduct Reaction with Hydroxylamine Hydrochloride and Hydrazine Hydrate : Formation of Oximes, Indazolones, Hydrazides, 2-Mercaotp-1,3,4,-Oxadiazoles, Imonobenzal-N-Amides of Cyclohexanones and Study of Their Antimicrobial - M. Rahatgaonkar, Anjali (Asian Journal of Chemistry, 2012)
A comparative study reveals that 1,2,4,5-tetrahydro-4-6-diaryl-in-dazoline-3-one-6-yl, 3,5-diaryl-6-carbohydrazide-2-ene-cyclo hexanone-3-yl and 3,5-diaryl-6-carbethoxy-2-ene cyclohexyl oxime were obtained by the reaction of 3,5-diaryl-6-carbathoxy-2-ene-cyclohexanone-3-yl with hydrazine hydrate and hydroxylamine hydrochloride in solvents S1, S2, S3 and S4 respectively. 3,5-Diaryl-6-carbohydrazide-2-ene-cyclohexanone-3-yl was further subjected to react with CS2/KOH and benzaldehydes to get 2-mercapto-1,3,4-oxadiazoles and Schiff bases respectively.